2021
DOI: 10.3390/rs13050844
|View full text |Cite
|
Sign up to set email alerts
|

SEVIRI Aerosol Optical Depth Validation Using AERONET and Intercomparison with MODIS in Central and Eastern Europe

Abstract: This paper presents the validation results of Aerosol Optical Depth (AOD) retrieved from the Spinning Enhanced Visible Infrared Radiometer (SEVIRI) data using the near-real-time algorithm further developed in the frame of the Satellite-based Monitoring Initiative for Regional Air quality (SAMIRA) project. The SEVIRI AOD was compared against multiple data sources: six stations of the Aerosol Robotic Network (AERONET) in Romania and Poland, three stations of the Aerosol Research Network in Poland (Poland–AOD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Validation against ground-based sun-photometers, located in Romania and Poland, using the data from 2014, showed generally good agreements with country mean correlation coefficients (R) between 0.61 and 0.62, a bias of 0.09-0.12, and an RMSE of 0.12-0.14, but did not correlate as well with the 3 km AOD product from MODIS. For more details see [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation against ground-based sun-photometers, located in Romania and Poland, using the data from 2014, showed generally good agreements with country mean correlation coefficients (R) between 0.61 and 0.62, a bias of 0.09-0.12, and an RMSE of 0.12-0.14, but did not correlate as well with the 3 km AOD product from MODIS. For more details see [64].…”
Section: Discussionmentioning
confidence: 99%
“…SEVIRI AOD did not correlate as well as with the 3 km AOD product from MODIS, with R and biases between 0.32 and 0.39, and 0.07 and 0.11, respectively. Detailed validation results for the individual AERONET and Poland-AOD sites, as well as map comparisons between SEVIRI and MODIS AOD, are given in [64]. The reference data for the validation of satellite-based PM 2.5 concentrations were PM 2.5 observations from the ground-based national air quality networks.…”
Section: Validation Of Seviri Aodmentioning
confidence: 99%
“…Extensive validation of the NRT SEVIRI retrieval of the AOD product and the AOD uncertainties was conducted by the University of Babes-Bolyai (Romanian SAMIRA partner) and it was described in [36]. Their study was focused on analyzing the correlations between the four-month long SEVIRI AOD dataset (June-September 2014, retrieved in a simulated NRT mode) and the temporally closest AOD data of both ground-based (AERONET, PolandAOD) and satellite (MODIS pixels) products.…”
Section: Example Of the Nrt Calculationsmentioning
confidence: 99%
“…Gupta et al [40] validated the global land surface Terra MODIS data set from 2000 to 2015 and the Aqua MODIS data set from 2003 to 2015 through AERONET data, and the results showed that Terra MODIS showed more changes over time. Ajtai et al [41] validated aerosol optical depth (AOD) from Spinning Enhanced Visible Infrared Radiometer (SEVIRI) data using data from six AERONET stations in Romania and the Baltic. Due to the limited availability of measured data over the ocean, in this study, we referred to the previous experience [42,43].…”
Section: Introductionmentioning
confidence: 99%